Design and Dynamic Analysis of Ideological and Political Education Platform Based on Network Multimedia Technology. (17th November 2022) - Chen, Xiaowen
Abstract : Network multimedia is a shape of mass media supported by the new technique system, and its main equipment includes mobile phones, notebook computers, and digital TVs. With the growth of science and technique, multimedia technique is also evolving rapidly and has got a section of people's activity. The emergence of network multimedia has introduced the technology of the new era into people's lives, which has had a significant influence on the thought-political teaching of today's learner. As a group of users in the "digital age", college students' thinking, behavior, and concept are all influenced by the multimedia network. The fast growth of multimedia network not only brings thought-political opportunities to students, but also brings problems. Because of the thought-political education platform design and ideological dynamic analysis of network multimedia technology, this study analyzes the construction and teaching circumstances of the platform, and then uses principal component analysis to analyze students' political theory, political attitude, civilized etiquette, observance of thought, collective thought, public welfare thought, analysis of learning ideas, get the eigenvalues and variance %, of which the proportion of variance of the first four principal components exceeds 90%; public welfare activities and the idea of abiding by laws and regulations have a better influence on the first main component; collective thinking has a comparison on the impact of the second principal component, the correlation between the indicators of thought-political education and the concept of students' quality is greater than 0.75; it shows that each index has a large degree of correlation with the concept of students' quality, among which Political attitudes have the greatest impact on students' quality outlook, with a correlation coefficient of 0.911; secondly, using a nonhomogeneous hidden Markov model to analyze ideological dynamics, we can get the learning situation in different ideological states; finally, the hot spots during the epidemic are related to ideological dynamics Sexual analysis showed that the p values were all less than 0.05, and the correlation analysis between hotspots and ideological dynamics during the epidemic was significant, namely "national sentiments", "social responsibility", "angels in white", "Chinese power", and "the benevolence of doctors". The hot words of "Youth Responsibility" have an active impact on the ideological state of learners, and their correlations are all above 0.7, and the correlation is strong. Network multimedia is a shape of mass media supported by the new technique system, and its main equipment includes mobile phones, notebook computers, and digital TVs. With the growth of science and technique, multimedia technique is also evolving rapidly and has got a section of people's activity. The emergence of network multimedia has introduced the technology of the new era into people's lives, which has had a significant influence on the thought-political teaching of today's learner.